Polarity Specific Effects of Cross-Hemispheric tDCS Coupled With Approach-Avoidance Training on Chocolate Craving - Carvalho, Sandra; Sampaio, Adriana; Mendes, Augusto J.; Lema, Alberto; Vieira, Daniela; Gonçalves, Óscar F.; Leite, Jorge (Frontiers in Pharmacology, 2019)
Transcranial Direct Current Stimulation (tDCS) over the Dorsolateral Prefrontal Cortex (DLPFC) has already been shown to decrease craving for food. However, it remains unclear whether a single session of tDCS combined with a cognitive bias modification (CBM) task may affect explicit and implicit measures of craving for chocolate. Fifty-one healthy volunteers (38 females; mean age: 22.12 ± 3.38) were randomly allocated to CBM training based on the Approach Avoidance task and either Sham, Right anodal-Left cathodal (RALC), or Left anodal-Right cathodal (LARC) tDCS. Results show that there was an increase in the explicit craving for chocolate, as assessed by the Visual Analogue Scale [F(2,46) = 3.239, p = .048], from the baseline to post intervention. Participants which received LARC tDCS were explicitly self-reporting more craving for chocolate than those that received RALC tDCS (p = .023). Moreover, this effect was also observed on the implicit measure [F(2,46) = 4.168, p = .022]. LARC tDCS significantly increased the implicit preference for chocolate when comparing to both RALC (p=0.009) and Sham tDCS (p=0.034). Previous studies have shown that RALC tDCS over the PFC is able to effectively decrease craving for food. Interestingly, the present data not only does not reproduce such result, but instead it suggests that LARC tDCS can actually increase the preference for chocolate. This result is compatible with recent models of brain laterality, in which cue craving seems to be more dependent on the left hemisphere. Thus, shifting the activity to the left hemisphere (while simultaneously reducing the activity over the homotopic region) may have led to this increased implicit as well as explicit preference for chocolate.